2011
DOI: 10.1111/j.1552-6909.2011.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Physical Activity of White Midlife Women

Abstract: Objective To explore attitudes toward physical activity of White midlife women in the United States using a feminist perspective. Design A cross-sectional qualitative study using a thematic analysis. Setting Internet communities for midlife women. Participants Twenty-nine White midlife women in the United States recruited using a convenience sampling method. Methods We used 17 topics on attitudes toward physical activity and ethnic-specific contexts to administer an online forum. We analyzed the data u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
1
27
1
2
Order By: Relevance
“…These findings on active living and sport/exercise activity may be supported by the ethnic differences in attitudes towards physical activity in midlife women. N-H White women regarded leisure-time physical activity as an essential for health, and had will to increase their physical activity (Im et al 2011b); thus, active participation in a leisure-time physical activity may positively impact psychosomatic menopausal symptoms. On the contrary, N-H Asian women placed less value on leisure-time physical activity, but actively participated in their daily routines (Im & Choe 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These findings on active living and sport/exercise activity may be supported by the ethnic differences in attitudes towards physical activity in midlife women. N-H White women regarded leisure-time physical activity as an essential for health, and had will to increase their physical activity (Im et al 2011b); thus, active participation in a leisure-time physical activity may positively impact psychosomatic menopausal symptoms. On the contrary, N-H Asian women placed less value on leisure-time physical activity, but actively participated in their daily routines (Im & Choe 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative follow-up study to a book club PA intervention, women reported that their increased knowledge (more aware about how to be active) was one of the most important attributes of their participation in the program (Huberty, et al, 2010). In another study, women reported they had ample information about PA via books, internet, but they needed in-depth information; topics detailing when or how to exercise and if what they were doing was the best for them (Im et al, 2011). More research related to knowledge about PA and its relationship to PA related SW is needed.…”
Section: [Insert Table 4 About Here] Discussionmentioning
confidence: 99%
“…These items reflect different stages of knowledge accumulation. Learning about physical activity and exercise can be fun and is essentially simple (representing declarative, lower-level knowledge), but developing a PA program (representing procedural, higher-level knowledge) may require more specific knowledge about PA--which a majority of adult women may not have (Im et al, 2011). Although beliefs, attitudes, and perceptions about PA and their relationship to PA participation in women have been studied extensively (Eyler, Matson-Koffman, Vest, Evenson, Sanderson, & Thompson et al, 2002a), knowledge about PA and its relationship to PA has not.…”
Section: [Insert Table 4 About Here] Discussionmentioning
confidence: 99%
“…A pesar de que las mujeres reconocen los beneficios del ejercicio y entienden la importancia de realizar AF, persiste la indisposición hacia ésa conducta promotora de salud. Im et al (2011) exploraron la perspectiva femenina hacia la AF de mujeres de media edad en Estados Unidos en un estudio cualitativo. Los autores señalaron que podría ser la influencia de aspectos culturales lo que impide la planeación y ejecución de AF (Im, Lee, Chee, & Stuifbergen, 2011 las creencias relativas a barreras para el ejercicio, aluden al alto costo económico que implica el realizar ejercicio, a la vergüenza percibida de realizar ejercicio a su edad y a la consideración de que el ejercicio físico es un trabajo duro.…”
Section: Discusió Nunclassified